Captive‐bred ancestry affects spatial patterns of genetic diversity and differentiation in brown trout (Salmo trutta) populations. Issue 9 (3rd May 2022) - Prunier, Jérôme G.; Saint‐Pé, Keoni; Tissot, Laurence; Poulet, Nicolas; Marselli, Geoffrey; Veyssière, Charlotte; Blanchet, Simon
Abstract: Intraspecific genetic diversity is heterogeneously distributed in natural landscapes and often forms repeatable spatial patterns. For instance, in rivers, genetic diversity increases towards downstream areas, whereas genetic differentiation increases in isolated upstream areas. Nonetheless, these patterns can be modified by human‐induced perturbations, and documenting the extent to which human activities alter these natural patterns is important for conservation. Among the human pressures that affect freshwater biodiversity, stocking natural populations with captive‐bred strains is a common practice worldwide that can strongly alter the genetic integrity of wild populations. The main objectives of this study were to document the spatial distribution of captive‐bred ancestry in brown trout ( Salmo trutta ) populations from four French basins having been stocked according to different practices, and to quantify for each basin the effect of captive‐bred ancestry on the spatial distribution of genetic diversity and differentiation. The four basins were sampled along their upstream–downstream gradient, and a total of 1, 686 individuals were genotyped at 192 single nucleotide polymorphism loci. For all basins, individuals with a strong assignment to the captive strain were mostly found in upper reaches, although the average proportion of captive‐bred ancestry varied strikingly among rivers (from 1.9 to 58.7%). Although spatial patterns of genetic differentiation were not affected by introgression and showed an expected increase with increasing distances from the river mouth in all basins, there was evidence that the classical pattern of downstream increase in genetic diversity was reversed when considering highly introgressed populations. These findings demonstrate that the stocking of captive‐bred strains can strongly modify natural spatial patterns of diversity, even when stocking occurred many generations ago and has now ended. The study illustrates the major impacts of humans on intraspecific biodiversity patterns, and emphasizes the importance of conservation plans that take into account this artificial distribution of genetic diversity.